2021
DOI: 10.1002/jcla.24101
|View full text |Cite
|
Sign up to set email alerts
|

Low serum interleukin‐38 levels in patients with Graves’ disease and Hashimoto’s thyroiditis

Abstract: Background Autoimmune thyroid disease (AITD) mainly includes Graves’ disease (GD) and Hashimoto's thyroiditis (HT), which is caused by individual genetics, autoimmune dysfunction, and a variety of external environmental factors. Interleukin (IL)‐38 is involved in a wide range of autoimmune diseases, but little is known about IL‐38 expression in AITD. Methods Fifty patients with GD, 50 with HT, and 50 healthy controls (HC) were enrolled in this study. Basic information of the participants was obtained through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Patients with atopic dermatitis ( 20 ), influenza ( 21 ), SLE ( 22 ), rheumatoid arthritis ( 25 , 39 ), myocardial infarction ( 23 ), sepsis ( 24 ), acquired immune-mediated neuropathies ( 31 ), osteoarthritis ( 32 ), acute respiratory distress syndrome ( 35 ), inflammatory bowel disease ( 33 ), type 2 diabetes ( 41 ), and vitiligo ( 43 ) present with higher blood concentrations of IL-38. This in contrast to e.g., patients with Graves’ and Hashimoto’s thyroiditis ( 44 ), Sjögren’s disease ( 34 ), Behçet’s disease ( 37 ), chronic brucellosis ( 40 ), and psoriasis ( 27 ), in whom IL-38 circulating concentrations were lower compared to healthy volunteers.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Patients with atopic dermatitis ( 20 ), influenza ( 21 ), SLE ( 22 ), rheumatoid arthritis ( 25 , 39 ), myocardial infarction ( 23 ), sepsis ( 24 ), acquired immune-mediated neuropathies ( 31 ), osteoarthritis ( 32 ), acute respiratory distress syndrome ( 35 ), inflammatory bowel disease ( 33 ), type 2 diabetes ( 41 ), and vitiligo ( 43 ) present with higher blood concentrations of IL-38. This in contrast to e.g., patients with Graves’ and Hashimoto’s thyroiditis ( 44 ), Sjögren’s disease ( 34 ), Behçet’s disease ( 37 ), chronic brucellosis ( 40 ), and psoriasis ( 27 ), in whom IL-38 circulating concentrations were lower compared to healthy volunteers.…”
Section: Discussionmentioning
confidence: 72%
“…Between September 2015 and December 2021 25 published studies ( Table 2 ) fulfilled the inclusion criteria as described in the Methods section ( 20 44 ). In order to determine the distribution of the collected data an overview figure was made ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“… 27 , 28 In GD, as in the current study, serum IL‐38 levels were significantly lower in patients than in CTRL, and the authors suggested that IL‐38 levels could be considered as a potential novel prognostic biomarker for GD. 12 Taken together, these findings suggest that IL‐38 may play roles in immune cell homeostasis with cytokine regulation as a mechanism involved in autoimmune diseases. Indeed, IL‐38 has been shown to be involved in regulating the differentiation and function of many immune cells, including T cells, PBMCs, macrophages, and dendritic cells, and thus may influence the development of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 90%
“… 11 Regarding GD, a recent study demonstrated that IL‐38 levels were significantly lower in patients than in controls and suggested the potential of IL‐38 as a new diagnostic biomarker for the disease. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in osteoarthritis patients, higher IL-38 levels indicated severe disease activity [ 27 ]. In Graves’ disease and Hashimoto’s thyroiditis, two types of thyroid inflammatory diseases, low serum IL-38 levels were observed [ 28 ]. These results suggest that IL-38 may exhibit anti- or pro-inflammatory actions in different pathological states, similar to its family members [ 15 ].…”
Section: Discussionmentioning
confidence: 99%